Heating and phyiso-mechanical characteristics of porous spinel developed by Starch - Saurav K.; Majhi M.R.; Singh V.K. (My University, 2025)
Among the techniques used to produce these materials (such as the addition of foaming agents and organic compounds), the pore generation via phase transformation presents key aspects, such as easy processing and the absence of toxic volatiles. In this study, this technique was applied to produce porous ceramics by decomposing an EX potato known as starch soluble (C6H10O5)n. Porous MgO ceramics prepared at different sintering temperatures is studied. Porous MgO was synthesis by heating pellets at 1100°C for 1hr. The resultant porous MgO was then immersed in an 10 mol/L aluminium nitrate solution, dried, and reheated at 1300°C for 2 hrs to convert it to spinel. The method results from generalized relations that were designed for study of physical properties of fractal structures. As it is shown these relations are in a good agreement with the equations used for the description of time responses of temperature for the pulse input of supplied heat. The volume fraction of porosity can be defined as the fraction of void space relative to the apparent total bulk volume of the sample. Porosity in materials originates from different processing and synthesis routes. © 2016, Hanyang University. All rights reserved.